Enculturation of A-Pik (Anti-Senile) Gymnastic Program in Bandung's Elderly Community - Afianti Sulastri; Mustika Fitri; Muhammad Zaky (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT Previous research has shown that A-Pik gymnastics improves cognition in healthy adults. Regular physical activity is related with healthier brains, enhanced memory, more effective planning, and other cognitive abilities, as well as a decreased chance of dementia. The brain continues to generate new cells and synapses throughout life, allowing us to continue learning. This skill is known as "brain plasticity." It is commonly known that the brain requires enough blood flow in order to receive sufficient oxygen and nutrients in order to function properly. Physical activity enhances the plasticity, survival, and development of brain cells, as well as their biological activities. This service initiative aims to offer APIK (Anti-senile) Gymnastics to senior citizens in the Bandung region. It is anticipated that after implementing this program, the elderly population will have enhanced physical and mental health. The socialization of the A-Pik Gymnastics program is conducted via videos uploaded to the A-Pik YouTube channel. Participants can learn the A-Pik gymnastics moves by using the URL provided, so individuals can practice whenever they like. Three times per week, the A-Pik gymnastics activities were conducted according to a predetermined timetable in order to track the participants' progress. Many passionate jumpers joined this program. Their enthusiasm for gymnastics shows this.  Keywords:Dementia, Cognitive Function, APIK (Anti-Pikun) Gymnastics